Origin of the tunable carrier selectivity of atomic-layer-deposited TiOx nanolayers in crystalline silicon solar cells - Matsui, T; Bivour, M; Ndione, PF; Bonilla, RS; Hermle, M (Elsevier, 2020)
Titanium oxide (TiOx) nanolayers grown by atomic layer deposition are investigated with respect to their application as carrier selective contacts for crystalline silicon (c-Si) solar cells. Although TiOx is known to act as an electron contact, in this work the selectivity of TiOx layers is found to be widely tunable from electron to hole selective depending on deposition conditions, post-deposition treatments, and work function of the metal electrode used. Using TiOx and an intrinsic hydrogenated amorphous silicon buffer layer, solar cell test structure exhibiting open-circuit voltages (Voc) as high as 720 and 650 mV are shown for electron and hole selective contacts, respectively. Surface photovoltage and capacitance-voltage measurements reveal that carrier selectivity is correlated with the amount of c-Si band bending induced by TiOx, which are governed not only by the effective work function difference at the Si/TiOx interface, but also by the negative fixed charge present in the TiOx layer. This new finding is in contrast to the previous model for carrier transport where selectivity is determined only by the asymmetric band offsets at the Si/contact interface. It highlights the influence of induced band bending to produce carrier depletion/inversion conditions, and the importance of its selectivity effect in a c-Si absorber.